Prevention of fungal infection in the early period after liver transplantation - M. Sh. Khubutiya (Transplantologiâ, 2016)
This article describes the risk and incidence of fungal infections in the early period after liver transplantation, their diagnosis, treatment and prevention. After liver transplant patients have a higher risk of developing invasive fungal infection. The presence of high - risk factors is an absolute indication for prophylactic antifungal medicine.